A note on Dichrostachys cinerea in South Africa - J. H. Ross (Bothalia: African Biodiversity & Conservation, 1974)
The nature o f the morphological variation within  Dichrostachys cinerea (L.) Wight  & Arn. in the area delimited for the Flora o f Southern Africa is discussed. An attempt is made to evaluate thetaxonomic significance o f some o f the differential characters employed by Brenan & Brummitt inBol. Soc. Brot., Sér. 2, 39: 61-115 (1965) in order to delimit the infraspecific taxa recorded from ourarea. Certain modifications to Brenan & Brummitt’s treatment are proposed.